2021
DOI: 10.3389/fneur.2021.669828
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Based Score of Early Ischemic Changes Predicts Malignant Infarction

Abstract: Background and Purpose: Identification of ischemic stroke patients at high risk of developing life-threatening malignant infarction at an early stage is critical to consider more rigorous monitoring and further therapeutic measures. We hypothesized that a score consisting of simple measurements of visually evident ischemic changes in non-enhanced CT (NEMMI score) predicts malignant middle cerebral artery (MCA) infarctions (MMI) with similar diagnostic power compared to other baseline clinical and imaging param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…15 Also, severity of hypoattenuation in infarcted tissue is correlated with worse prognosis, 16 and malignant edema. 17 In our study, no reversal of hypoattenuation was observed and all baseline ischemic changes were also detectable at 24 h (and also in any subsequent CT scan taken during the hospitalization). The same phenomenon was described in the early 2000s.…”
Section: Discussionsupporting
confidence: 42%
See 2 more Smart Citations
“…15 Also, severity of hypoattenuation in infarcted tissue is correlated with worse prognosis, 16 and malignant edema. 17 In our study, no reversal of hypoattenuation was observed and all baseline ischemic changes were also detectable at 24 h (and also in any subsequent CT scan taken during the hospitalization). The same phenomenon was described in the early 2000s.…”
Section: Discussionsupporting
confidence: 42%
“…Their median age was 71 [IQR 62-79] years and 45% were females. Baseline NIHSS was median 14 [8][9][10][11][12][13][14][15][16][17][18]. Time from last-seen-well to arrival was median 170 [73-347] minutes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…41 Recently, a score calculated as the sum of the measurement of the maximum anteroposterior and mediolateral diameter of infarction multiplied by visually graded assessment of hypodensity on admission noncontrast CT (NEMMI score) was found to be useful to predict malignant MCA infarction. 42 In one study, the ability of the NEMMI score to predict malignant transformation was higher than patient's age, stroke severity, and infarct volume. 42 This could be important in an emergency, as the score is not dependent on any other clinical or laboratory characteristics.…”
Section: Prediction Scores For Malignant Edemamentioning
confidence: 98%
“…42 In one study, the ability of the NEMMI score to predict malignant transformation was higher than patient's age, stroke severity, and infarct volume. 42 This could be important in an emergency, as the score is not dependent on any other clinical or laboratory characteristics. More research is needed to validate these results with interobserver agreement.…”
Section: Prediction Scores For Malignant Edemamentioning
confidence: 98%